Effects of Shenfu injection on intestinal microbiota and inflammation in sepsis mice - Li, Ning; Yi, Fan; Wang, Yujun; Geng, Feng; Liu, Yanli; Liu, Qiushuang; Guo, Yanan; Long, Ding (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionSepsis remains a critical challenge in intensive care medicine, necessitating novel therapeutic approaches. MethodsIn this study, healthy 8-week-old male C57BL/6J mice were treated with cecal ligation and puncture (CLP) to induce a sepsis model. After successful model establishment, mice in the sham and CLP groups were injected with 200 μL of normal saline, while mice in the SFI group were injected with 200 μL of SFI. Changes in intestinal mucosal barrier function, inflammation, and intestinal microbiota were assessed in septic mice after SFI treatment.ResultsSFI treatment significantly ameliorated intestinal inflammation and reduced serum levels of pro-inflammatory cytokines (IL-1β, IL-6) and renal injury markers (SCr, BUN). 16S rRNA sequencing revealed SFI-mediated gut microbial remodeling, characterized by a marked reduction in pathogenic Escherichia-Shigella abundance and concurrent enrichment of beneficial probiotics, including Akkermansia and Lactobacillus. Mechanistically, SFI exhibited dual regulatory effects on both systemic inflammation and gut microbiota homeostasis.DiscussionThese findings not only validate SFI's efficacy in sepsis treatment but also propose a novel mechanism involving gut microbiome modulation. This study provides critical experimental evidence for repurposing traditional Chinese medicine in sepsis therapy and establishes a foundation for future research on microbiota-targeted interventions in critical care.